Addicted to lust: pornography in the lives of conservative Protestants - Perry, Samuel L. (Oxford University Press, 2019)
From obscenity outside to addiction within -- Fifty shades of gray area? On masturbation -- Fleshly lusts that war against the soul -- Every man's battle? -- Till porn do us part -- So help me God (or whatever works).